Statistical analysis of equatorial electrojet responses to the transient changes of solar wind conditions - Zhang, Jiawei; Li, Qiaoling; Li, Shuhan; Liu, Jing (Frontiers in Astronomy and Space Sciences, 2023)
Prior case studies have indicated that changes in solar wind conditions have a significant impact on equatorial ionospheric electrodynamics. However, there have been limited statistical studies on this topic, impairing our understanding of the coupling between solar wind, magnetosphere, and equatorial ionosphere electrodynamics. In this study, we conducted a superposed epoch analysis of long-term data from the South America equatorial electrojet (EEJ) spanning from 2001 to 2021 examining the responses of the equatorial ionospheric electric field to step-like changes in solar wind velocity, density, dynamic pressure, and interplanetary magnetic field (IMF) Bz. Our study shows that step-like changes in solar wind velocity, density, and dynamic pressure can trigger changes in EEJ within ~20-40 minutes. EEJ exhibits the highest sensitivity to variations in solar wind velocity while being relatively less sensitive to changes in dynamic pressure. Furthermore, the response of EEJ shows greater responsiveness to northward IMF Bz compared to southward IMF Bz. Our work provides statistical evidence of how changes in solar wind can lead to changes in low-latitude ionospheric EEJ. We inferred that the changes in solar wind conditions cause magnetospheric deformation and changes in magnetic reconnection rates, leading to the fluctuations of the ionospheric electric field and the resultant EEJ variations.